Do adsorbent pore size and specific surface area affect the kinetics of methyl orange aqueous phase adsorption? - Kingsley Iwuozor; Joshua Ighalo; Ebuka Emenike; Chinenye Igwegbe; Adewale Adeniyi (Journal of Chemistry Letters)
The kinetics of any adsorption reaction gives more information on the rate at which the adsorbate is taken up by the adsorbent, which is responsible for the residence time of an adsorbate uptake at the adsorbent-aqueous phase interface. This study was aimed at determining the effect of pore size as well as specific surface area (SSA) on the kinetics of the uptake of methyl orange (MO). The basis of the analysis was from data on kinetic models sourced from recent literature. ANOVA of the data revealed that statistical significance was achieved for SSA but not for pore size (at a significance level of 0.05). This called for a more theoretical perspective on the research data. The kinetics constant for micropores is far higher than for the two selected regimes of the mesopore. For the SSA, 100 – 10 m2/g adsorbents had a higher mean k_2 value. This suggested that adsorbents in the SSA range had pore sizes that favour rapid uptake. However, further studies will be needed to gain a better understanding of how SSA affects adsorption kinetics. The study also discussed the technical limitations that could arise due to the use of kinetic model linearisation.